Cover Image, Volume 32, Issue 8. (6th August 2021) - De Martino, Giuseppe; Compagnucci, Paolo; Mancusi, Carmine; Vassallo, Enrico; Calvanese, Claudia; Della Ratta, Giuseppe; Librera, Mariateresa; Franciulli, Marco; Marino, Luigi; Russo, Antonio Dello; Casella, Michela
Abstract : The Back cover image is based on the Original ‐ Electrophysiology Stepwise endo‐/epicardial catheter ablation for atrial fibrillation: The Mediterranea approach by Giuseppe De Martino et al., https://doi.org/10.1111/jce.15151 .